Excessive Volatility in Asia Stock Market Around General Election (GE) Period - Aik, Nai-Chiek; Ng, Kean-Kok (Asian Journal of Empirical Research, 2015)
A sample of eleven Asia countries’ Morgan Stanley Capital International Incorporation (MSCI) index was collected from year 1972 to year 2010. The results of cumulative abnormal volatility (CAV) based on GARCH (1, 1) model show that there is excessive volatility up to 25 days before and after the GE in these Asian stock markets, suggesting the Asia stock markets are weak form inefficient. Further findings in this study reveal that market participants react conservatively to the change in political condition and causing abnormal fluctuation in stock market movement.